1990
DOI: 10.1007/bf02624474
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of psoriatic cell proliferation in in vitro skin models by amiprilose hydrochloride

Abstract: Amiprilose hydrochloride, a 3-substituted glucose derivative, was found to inhibit the proliferation of human fibroblasts and keratinocytes originating from psoriatic lesions. Fibroblasts and keratinocytes were obtained from skin biopsies of normal donors, and from the biopsies of active/involved and uninvolved sites of psoriatic donors. The cells were cultured as monolayers or as components of tissue equivalent models. Keratinocytes and fibroblasts originating from biopsies of psoriatically involved areas wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Animal models, however, can prove unsatisfactory, as allogeneic differences can cause artifactual immune responses, furnished by the xenograph, which may differ from that of psoriasis. Various attempts to model aspects of the disease in vitro have been reported, using both monolayer and stratified keratinocyte cultures (Saiag et al, 1985;Chapman et al, 1990;Mils et al, 1994;Van Ruissen et al, 1996a, b;Pol et al, 2002). Some previous studies have demonstrated the importance of crosstalk between the keratinocyte and the fibroblast in modeling the disease in vitro (Krueger and Jorgensen, 1990;Konstantinova et al, 1996;Krueger and Jorgensen, 1997).…”
mentioning
confidence: 94%
“…Animal models, however, can prove unsatisfactory, as allogeneic differences can cause artifactual immune responses, furnished by the xenograph, which may differ from that of psoriasis. Various attempts to model aspects of the disease in vitro have been reported, using both monolayer and stratified keratinocyte cultures (Saiag et al, 1985;Chapman et al, 1990;Mils et al, 1994;Van Ruissen et al, 1996a, b;Pol et al, 2002). Some previous studies have demonstrated the importance of crosstalk between the keratinocyte and the fibroblast in modeling the disease in vitro (Krueger and Jorgensen, 1990;Konstantinova et al, 1996;Krueger and Jorgensen, 1997).…”
mentioning
confidence: 94%
“…Development of “tissue equivalents,” as in vitro models of living tissue, provides an opportunity to study some of these processes in a more systematic and quantifiable fashion. We have developed a noncontracting human skin equivalent (HSE, NexMed, Inc., Robinsville NJ), 24 which has proven an invaluable tool in evaluation of potential topical pharmaceutical agents 25,26 . A particularly useful feature of our model is its translucence which allows the status of the cellular and extracellular components to be evaluated nonintrusively by light microscopy.…”
mentioning
confidence: 99%
“…We have developed a noncontracting human skin equivalent (HSE, NexMed, Inc., Robinsville NJ), 24 which has proven an invaluable tool in evaluation of potential topical pharmaceutical agents. 25,26 A particularly useful feature of our model is its translucence which allows the status of the cellular and extracellular components to be evaluated nonintrusively by light microscopy. The goal of the studies described here was to utilize human cell monolayers as well as dermal and skin equivalents (DEs and SEs) to evaluate systematically the cellular and molecular responses to hyperbaric oxygen.…”
mentioning
confidence: 99%
“…Psoriasis is characterized by red and scaly plaques on the skin with a predilection for certain areas (elbows, knees and scalp) (Chapman et al, 1990;Lowes, et al, 2007). There are five clinical variants of psoriasis: guttate, erythrodermic, pustular, inverse and psoriasis vulgaris, the last of wich is the most common type seen in approximately 90% of patients (Fitzpatrick and Wolff, 2008).…”
Section: Characteristicsmentioning
confidence: 99%